Modernist Alchemy : Poetry and the Occult - Materer, Timothy, 1940- (Book collections on Project MUSE., 1995)
Materer ends with Merrill, whose attempt to suspend both doubt and belief marks the culmination of the poetic style initiated by Yeats.